Food consumption, feeding habits, and growth of walleye (Stizostedion vitreum) and sauger (Stizostedion canadense) in the Ottawa River near Ottawa-Hull, Canada. - Osterberg, Donald M. (University of Ottawa (Canada), 1978)
Food consumption and growth of walleye, Stizostedion vitreum (Mitchill) and sauger, Stizostedion canadense (Smith) were compared. Both the species were caught in the Ottawa River during 1967 to 1972. Their daily feeding periods, feeding behavior, and movement were studied from spring to fall in the field. Growth of the walleye and sauger in the Ottawa River was the lowest recorded for any water of similar latitude. Slow growth was pronounced in fish older than three years. For example, the mean total lengths of six year old walleye and sauger were 40.2 cm and 29.4 cm respectively as compared to 49 cm (Balch, 1951) and 41 cm (Van Oosten, 1948) for walleye and sauger of the same age from the Great Lakes. Sauger consume demersal prey due to their sensitivity to light intensity. However, in the Ottawa, River, a lack of sufficient prey in demersal waters caused the sauger to com pete ineffectively for food with the walleye and non-Stizostedion predators in the littoral zone of the river. We observed that the emerald shiner (Notropis atherinoides) was the most abundant prey species in the littoral zone, accounting for more than 75% of the diet of the walleye and sauger. Yellow perch (Perca flavescens), also caught in the littoral zone, served as an important secondary food source during periods of low density of the emerald shiner. Daily food consumption of walleye in the river decreased from 4.3 to 3.0% of body weight in two to six year old fish. Daily food consumption of the sauger decreased from 3.3 to 2.9% of body weight in two to six year old fish. In the laboratory, two, three, and four year old walleye and sauger, when fed ad libitum, consumed more food per day (4-9% of body weight) than fish of the same age in the river. Approximately two thirds of the total walleye and sauger moving into the feeding area in the river were caught between sunset and midnight. Most of the remaining one third were caught before 3 a.m.. Daily food consumption and growth of the fish in the river indicated that both species must have fed every night during the growing season. Feeding activity of the walleye peaked in late July and coincided with the highest prey density. Feeding activity of the sauger peaked in August. In the laboratory, walleye and sauger differed very little with respect to food consumption, stomach and gut evacuation time, efficiency of food assimilation, and growth efficiency. Stomach evacuation at 19°C took an average of 18 hours, and food passed through the entire digestive tract in 48 hours. Ingested calories were assimilated with an efficiency of 92%. Food conversion efficiency for growth ranged between 13 and 15% for two and three year old fish fed at 4.0% of body weight and maintained at 19°C in the laboratory. Continued disruption of their habitat, e.g. dam construction and increased eutrophication, threatens the balance between the two species and may cause the disappearance of the sauger in the Ottawa River as it did in the St. Lawrence River. Only good fishery management practices can avert this situation.
Keywords: Biology, Animal Physiology.